2016
DOI: 10.14444/3043
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Gross and CT measurements of Cadaveric Cervical Vertebrae (C3 – C6) as Guidelines for the Lateral mass screw fixation

Abstract: BackgroundLateral mass screw fixation is the treatment of choice for posterior cervical stabilization. Long or misdirected screws carry a risk of injury to spinal nerve roots or vertebral artery. This study was aimed to assess the gross anatomic and CT measurements of typical cervical vertebrae for the selection of lateral mass screws.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Neurologic injury can also be caused by insertion of long screws leading to a disruption of the ventral cortex of the lateral mass. The oblique antero-posterior (OAP) diameter of the articular pillar is representative of the screw length by Magerl method with average OAP diameter reported from 10.8 mm to 20.3 mm with a mean of 14.9 mm ± 1.8 as reported by Sangari et al 15 similar to our study where we used screw between12to 14 mm. Even, aiming the screw anteromedially rather than anterolaterally can lead to penetration of the transverse foramen and thus vertebral artery injury.…”
Section: Discussionsupporting
confidence: 87%
“…Neurologic injury can also be caused by insertion of long screws leading to a disruption of the ventral cortex of the lateral mass. The oblique antero-posterior (OAP) diameter of the articular pillar is representative of the screw length by Magerl method with average OAP diameter reported from 10.8 mm to 20.3 mm with a mean of 14.9 mm ± 1.8 as reported by Sangari et al 15 similar to our study where we used screw between12to 14 mm. Even, aiming the screw anteromedially rather than anterolaterally can lead to penetration of the transverse foramen and thus vertebral artery injury.…”
Section: Discussionsupporting
confidence: 87%
“…These factors should be considered when performing anatomical analyses, although only one study was found to have considered these points (Stemper et al, 2008). Since the Roy–Camille and Magerl techniques require complex decision‐making regarding the direction of screw insertion, precise 3D reconstruction is highly recommended for accurate analysis, of which the examples are very few (Sangari et al, 2016). Our analysis took sex factors into careful consideration, particularly those that could potentially cause differences in cervical spine morphology.…”
Section: Discussionmentioning
confidence: 99%
“…The limitation of this study is that the measurements were performed by a single neurosurgeon, and that majority of the previously published papers has not been performed by multiple observers (Cho & Kim, 2008; Ebraheim et al, 1998; Hockel et al, 2014; Mohamed et al, 2012; Yoon et al, 2004). If possible, the measurement by two or more observers can potentially improve inter‐observer reliability, and such approach was applied in only two of the previous studies (Sangari et al, 2016; Stemper et al, 2008). Apparently, our results do not show significant contradiction to past studies results, but methodologically we should consider it as deficiency despite of enough intra‐observer repeatability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations